The Economic Viability of the Renewable Energy Systems in Agricultural Activities in Jordan - AL-Dalaeen, Jawad (Jordan Journal of Agricultural Sciences, 2024)
This study aimes to study the economic viability of using renewable energy sources in different agricultural farms and activities. The economic viability was investigated according to the farm activities, size, and type of renewable energy source. A cross-sectional study was used by questionnaire for data collection. The questionnaire included two parts; the first part covered farm characteristics, while the second one covered the economic viability of renewable energy systems in the agricultural business. The questionnaire was distributed to a random sample of 100 farmers in different areas. The collected questionnaires were isolated and analyzed using the R software. Descriptive and inferential analyses were used to obtain the final results of the study. The results showed that the use of renewable energy system is viable in the agricultural sector. The economic viability increases as the size of the farm increases. The results showed that the cost-benefit ratio, the net present value, and the internal rate of return were the highest for the farms of 500 dunums and more. Solar radiation was found as the viable source that is widely distributed among farmers, followed by wind energy, and the least was recorded for biomass energy. The results showed that renewable energy sources are not sufficient to cover farm energy needs. In addition, the use of renewable energy systems was more viable in animal production farms and farms practicing both animal and plant production processes. The use of renewable energy was economically viable with different levels in all farms in the agricultural business. The economic viability increases in farms with mixed animal and plant activities. The study recommended that the government encourage the use of renewable energy systems to increase the farms’ energy independence and protect the environment.